YOUTUBE SEBAGAI SARANA LITERASI DEMOKRASI MAHASISWA ILMU KOMUNIKASI UMRI - Wahyu Ramadhan Chaniago; Diaz Sari; Muhammad Raihan; Naufal Hanif Muzakki; Syanaz Oktavia Ramadana (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study explores the perceptions and experiences of Communication Science students at Universitas Muhammadiyah Riau in utilizing YouTube as a medium for democratic literacy. Using a descriptive qualitative approach, data were collected through in-depth interviews with six students and open-ended questionnaires. The findings reveal that students perceive YouTube as an effective educational platform for conveying democratic values in an engaging and up-to-date manner. Channels such as Narasi, Najwa Shihab, and BBC Indonesia enrich students' political understanding, foster critical thinking, and enhance democratic participation. However, students acknowledge the need for critical content evaluation due to the potential for bias and misinformation. These findings highlight YouTube’s significant role as an informal learning tool in strengthening democratic literacy among the youth. Keywords: Democratic literacy, Student, Youtube.